Electrochemical immunoassay for detection of hepatitis C virus core antigen using electrode modified with Pt-decorated single-walled carbon nanotubes - Pusomjit, Pannaporn; Teengam, Prinjaporn; Chuaypen, Natthaya; Tangkijvanich, Pisit; Thepsuparungsikul, Nichanan; Chailapakul, Orawon (Mikrochimica acta (1966), 2022)
Pt nanoparticles deposited on single-walled carbon nanotubes (PtSWCNTs), synthesized via the deposition precipitation (DP) method, were introduced as a substrate for immobilizing antibodies on an electrode surface and then enhancing the electrochemical sensitivity. A PtSWCNT-modified paper-based screen-printed graphene electrode was successfully developed to diagnose hepatitis C virus (HCV) infection. The hepatitis C virus core antigen (HCV-cAg) level was determined by differential pulse voltammetry (DPV) using [Fe(CN) 6 ] 3−/4− as a redox solution. In the presence of HCV-cAg, the DPV current response decreased with increasing HCV-cAg concentration. Under the optimal conditions, the change in current response provides a good linear correlation with the logarithm of HCV-cAg concentration in the range 0.05 to 1000 pg mL −1 (RSD < 5%), and the limit of detection was 0.015 pg mL −1 (or 0.71 fmol L −1 ). Furthermore, the proposed immunosensor has been utilized to quantify HCV-cAg in human serum samples with reliable results compared with standard immunoassays (% relative error < 10%). This sensor offers a simple, sensitive, selective, disposable, and inexpensive means for determination of HCV-cAg in human serum samples. The paper-based label-free immunosensor is versatile and feasible for clinical diagnosis. Graphical abstract